2019
DOI: 10.1007/s00586-019-06108-9
|View full text |Cite|
|
Sign up to set email alerts
|

Disc inflammation and Modic changes show an interaction effect on recovery after surgery for lumbar disc herniation

Abstract: Purpose To study the interaction between Modic changes (MC) and inflammation by macrophages in the disc, in relation to clinical symptoms before and after discectomy for lumbar disc herniation. Methods Disc tissue was embedded in paraffin and stained with haematoxylin and CD68. Subsequently, tissue samples were categorized for degree of inflammation. Type of MC was scored on MRI at baseline. Roland Disability Questionnaire (RDQ) score and visual analogue scale for back pain and leg pain separately were conside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 26 publications
1
29
1
Order By: Relevance
“…7 The disc is avascular with sparse nerve distribution and lacks a strong physiological basis as a primary pain generator. 8 Over years, the attention has therefore shifted to other anatomical structures like endplates to explain the etiological basis of LBP. 9 Vertebral endplate is a thin interface between bone marrow (BM) and disc; and any loss of its integrity can potentially trigger a cascade of degenerative events.…”
Section: Low Back Pain and Historic Background Of MCmentioning
confidence: 99%
See 1 more Smart Citation
“…7 The disc is avascular with sparse nerve distribution and lacks a strong physiological basis as a primary pain generator. 8 Over years, the attention has therefore shifted to other anatomical structures like endplates to explain the etiological basis of LBP. 9 Vertebral endplate is a thin interface between bone marrow (BM) and disc; and any loss of its integrity can potentially trigger a cascade of degenerative events.…”
Section: Low Back Pain and Historic Background Of MCmentioning
confidence: 99%
“…Increased number of PGP-9.5 nerve fibers and TNF-a positive cells inside MC type I and II endplates may contribute to endplate-origin pain. 86e88 Djuric et al 8 demonstrated the importance of signs of disc inflammation in MC. They showed that patients with preoperative disc inflammation had less satisfactory outcome after discectomy.…”
Section: And Surgical Treatmentmentioning
confidence: 99%
“…This makes the disc prone to neovascularisation and macrophage infiltration, which is often seen in cervical and lumbar discs [ 2 , 3 ]. Macrophage infiltration of the extruded material could promote a foreign body response and thereby worsen the symptoms [ 4 ]. However, they can also help to resorb the herniated material and thus alleviate the symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous work, we found that the impact of the presence of macrophages on clinical outcomes was dependent on the presence of Modic changes (MC), which are considered inflammatory vertebral endplate signal changes that occur frequently on cervical and lumbar endplates [ 10 , 11 ]. We found that in patients with MC, a higher degree of macrophage infiltration, was accompanied by more radicular pain symptoms and less favourable clinical outcomes [ 4 ]. In addition, we also showed that in patients without MC, a higher degree of macrophage infiltration was associated with less radicular pain and a better clinical outcome [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation